Exploring Scaffolding In Teaching English At SMP Yapend Makassar - Isnaini Achmad Renaldi; Amirullah Abduh; Abdullah (International Journal of Language, Education, and Literature, 2025)
This study investigates the implementation of scaffolding strategies in teaching English at SMP Yapend Bungaya Makassar, focusing on teachers’ perceptions and instructional practices. The research aims to: (1) How is the teacher perception about scaffolding learning strategies in teaching English at SMP Yapend Bungaya Makassar? (2) How does the teacher apply scaffolding in teaching English at SMP Yapend Bungaya Makassar?. This qualitative study employs a case study approach, with data collected through observation, interviews, and documentation. The subject of the study is an English teacher at SMP Yapend Bungaya Makassar.The findings reveal that teachers hold both positive and negative perceptions toward scaffolding in English instruction. On the positive side, scaffolding is seen as an effective approach to enhance student motivation, foster engagement, and support gradual understanding of complex materials. However, challenges such as time constraints and the need to balance assistance for students with varying proficiency levels were also reported.In practice, the application of scaffolding follows three main stages in accordance with Bruner’s modes of representation: (1) Enactive stage—hands-on tasks involving real objects to build concrete understanding; (2) Iconic stage—the use of visual storytelling and simple multimedia tools to aid comprehension; and (3) Symbolic stage—guided practice that gradually leads students to independent use of the English language through verbal prompts, written exercises, and feedback.The study concludes that scaffolding is a well-implemented and beneficial teaching strategy at SMP Yapend Bungaya Makassar. It provides meaningful support for students to progress from dependence to independence in their language learning journey. This strategy is particularly relevant in the context of the Kurikulum Merdeka, which emphasizes student-centered and differentiated learning. The research contributes to the growing body of literature on scaffolding in classrooms and offers practical insights for English teachers seeking to improve instructional practices.